Dilemma in diagnosing a post-auricular mass-angiolymphoid hyperplasia with eosinophilia versus Kimura’s disease, an infrequent encounter - Shetty, Sandeep; Chandrashekar, Shilpa; Ganesan, Nivetha Devi; Dey, Debayan; Bhaskarachar, Ramya Sathanur (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Angiolymphoid hyperplasia with eosinophilia (ALHE) and Kimura’s disease are uncommon chronic benign lesions of the skin mainly involving the head and neck regions where ALHE involves vascular and lymphocytic proliferation and Kimura’s is of inflammatory type. Dermal involvement is more in ALHE but In Kimura’s disease the lymphnodes and subcutaneous tissues are involved more. ALHE is a rare vascular tumor and Kimura’s disease is a chronic inflammatory disease. Both not only have uncertainty in etiology and pathogenesis, but also there is therapeutic dilemma in management. In this article, we describe a case of ALHE which presented to our ENT outpatient department with swelling in the left postauricular region which appeared 1.5 years back and posed a riddle in coming to correct diagnosis. On examination, a single smooth spherical swelling in upper part of post-auricular region of size 3×3 cm with well-defined edges and normal skin. Blood investigations revealed elevated absolute eosinophil count. HRCT temporal bone showed a well-defined rounded hypo-dense lesion measuring 28×23 mm with no effect of adjacent bony erosion / calcifications/ cystic changes suggestive of benign etiology. FNAC showed scantly cellular and occasionally scattered fibroblasts, pinkish stromal collagen fragments with inflammatory cells in background of haemorrhage suggestive of soft tissue neoplasm.